Coronary Stent Abscess in the Setting of Arteriovenous Graft Infection following COVID-19: An Autopsy Case Report - Jean Thompson Butler; Rajeshwari Chellappan; Silvio Litovsky; Sixto M. Leal; Paul V. Benson (Hindawi Limited, 2023)
While rare, coronary stent infections present with significant mortality-with most infections and further complications occurring within months of percutaneous coronary intervention (PCI). Here, we discuss a post-COVID-19 patient who presented approximately one year after PCI for declotting of an arteriovenous graft (AVG). Upon admission, the patient was found to be bacteremic with multilobar pneumonia and an infection of the AVG. Empiric antibiotics were started, and blood cultures were subsequently positive for MRSA. Removal of the AVG was unsuccessful, and two days after admission, the patient passed. Autopsy revealed a perivascular abscess in the RCA near the origin of the stent with a ground section of the RCA with stent revealing abundant calcific atherosclerosis and marked necrosis of the artery wall. The cause of death was determined to be sepsis complicating coronary artery disease and chronic renal failure.